Peningkatan Profesionalisme Guru Melalui Pelatihan Pembelajaran Aktif - Riadi, Bambang (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2017)
Abstract In West Lampung regency, some teachers have not yet implemented active learning in their classrooms. It was due to their lack of understanding towards various models of active learning. Thus, to improve teachers’ professionals in the field of teaching, a training of active learning was much needed. The results of the training showed that the average score of their pre-test was 59, and that of post-test was 87 that it can be said that there was an increase after the training. In addition, the results of microteaching assessment resulted in an average score of 3.47 which fell into good category. It means that teachers have achieved good understanding on active learning and the capability to implement it. The teachers participating in the training were also satisfied with the service of the committee and speakers. Therefore, it can be concluded that the training on active learning succeeded in achieving the expected goals. Key words: active learning, teachers, training Di Kabupaten Lampung Barat, sebagian guru belum menerapkan pembelajaran aktif. Hal ini disebabkan ketidaktahuan mereka terhadap berbagai model pembelajaran aktif. Dengan demikian, untuk meningkatkan profesional guru dibidang pengajaran, guru-guru memerlukan pelatihan pembelajaran aktif. Hasil pelatihan ini menunjukkan bahwa hasil pretes dan postes diperoleh skor rata-rata yaitu 59 dan 87 sehingga dapat dikatakan kemampuan peserta pelatihan terlihat meningkat. Hasil penilaian saat microteaching diperoleh skor rata-rata sebesar 3,47 dengan kategori baik. Hal ini berarti bahwa guru telah memiliki pemahaman tentang pembelajaran aktif dan mampu menerapkan pembelajaran aktif. Selain itu, peserta pelatihan merasa puas terhadap pelayanan panitia dan strategi/bimbingan fasilitator. Dengan demikian, Pelatihan ini berhasil mencapai tujuan yang diharapkan secara maksimal. Kata kunci: active learning, guru, pelatihan